The Impact of Stellar Initial Mass Function on the Epoch of Reionization: Insights from Semi-Analytic Galaxy Modeling - Qingbo Ma; Lei Liu; Peiai Liu (Universe)
The adequate choice of stellar initial mass function (IMF) is crucial when studying high-z galaxy formation and the epoch of reionization (EoR) models. We employ the semi-analytical galaxy model L-Galaxies2020 and the dark matter simulation Millennium-II, in combination with the BPASS spectral model, to investigate the effects of different stellar IMFs on the properties of high-z galaxies and their ionizing photon budget during EoR. We find that different stellar IMFs lead to different SED of high-z galaxies, and thus different ultraviolet luminosity functions (UVLF) and budgets of ionizing photons for EoR. Specifically, at <semantics>z<10</semantics>, the UVLF with Salpeter and Chabrier IMF models are closer to the observed results, while at <semantics>z>10</semantics>, the ones with a Top-Heavy model are more consistent with the JWST observations. The increase in the upper limit of star mass within stellar IMF from <semantics>100<mspace width="0.166667em"></mspace>M⊙</semantics> to <semantics>300<mspace width="0.166667em"></mspace>M⊙</semantics> results in the increase in the UVLF and the ionizing photon number density.